Thermodynamics in Mineral Sciences An Introduction - Cemic, Ladislav (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Thermodynamics is an important tool to interpreting the conditions at which natural geomaterial equilibrate. It allows one to determine, for example, the equilibrium pressures and temperatures and the nature and chemical composition of phases - volved mineralogical and petrological processes. Simple chemical model systems, which are often studied in the laboratory in order to understand more complicated natural systems, generally consist of few chemical components. In order to use phase equilibrium results obtained from model systems for interpreting the con- tions of formation of natural geologic materials, extrapolations in compositional space and other P-T conditions are often required. This can only be done using the mathematical formalism that is offered by thermodynamics. An number of excellent books on thermodynamics with regards to the fields of mineralogy, petrology and geochemistry have been published over past 40 years. Many of them are, however, written for more advanced students and experienced - searchers and it is often assumed that the reader already possesses some prior knowledge of the subject. Consequently, discussions and presentations of basic c- cepts, which are necessary for beginning students and others attempting to learn thermodynamics for the first time, are often given short shrift. Therefore, the aim of this book is to explain the basic principles of thermodynamics at an introductory l- el, while trying not to loose much of the mathematical rigor that is one of the most important and central aspects of this subject.